The evaluation of accident data by using existing predictive model for Johor and Selangor state - Abd Rahman, Raha; Abdul Khair, Muhammad Aizat; Wei May, Lim; Mohd Masirin, Mohd Idrus; Hassan, Mohd Farid (Science and Engineering Research Support Society, 2020)
Road accidents are common inevitable occurrences over the world, in average Malaysia estimated 19 persons are killed every single day. The two states contributing to Malaysia’s highest fatal accidents are Selangor and Johor. In the year 2017, Selangor and Johor recorded respectively 154,958 and 76,121 accidents as well as fatalities of 1,087 and 1,067 cases. This study evaluates these accident data for the states of Johor and Selangor with existing predictive models. Fatalities are predicted for both states in 5 years from 2019 until 2024. The accident data can be studied in relation to the type of fatality includes serious injury, slightly injury and damage or with the dependent variables of vehicle type and number of registered motor vehicle. The study found that the analysis from Rehan’s model and Aminuddin’s model produced sounding results among the studied predictive models. The findings from Rehan’s model predictions are preferable and the predicted trends shows that by 2025, there will be 2,743 fatalities due to road accidents in the state of Selangor and 2,346 in Johor and can be related to the results of increasing population and vehicles in the states.